Underpotential Photoelectrooxidation of Water by SnS2−Laccase Co‐catalysts on Nanostructured Electrodes with Only Visible‐Light Irradiation. Issue 10 (21st May 2019) - Jarne, Carmen; Paul, Logan; Conesa, José Carlos; Shleev, Sergey; De Lacey, Antonio L.; Pita, Marcos
Abstract: More sustainable ways to produce and store energy are urgently needed to reduce our dependence on fossil fuels, which are the principal drivers of global warming and pollution. Hydrogen may become the energy vector needed for this purpose if its production through water splitting can become competitive against steam methane reforming. Even after decades of research, the proposed strategies for water splitting are not efficient enough to overcome the high overpotential of the water oxidation reaction. In a quest for new approaches to this problem, recent studies have attempted to combine inorganic catalysts with biocatalysts, aiming to open new possibilities towards a definitive solution. In the present work we have tested a chalcogenide semiconductor, SnS2, characterized by a deep valence band and a visible‐light band gap of approximately 2.2 eV (λ=550 nm). Preparation of a fluorine‐doped tin oxide electrode modified with SnS2 and laccase allowed water oxidation at a lower overpotential, taking better advantage of light energy. Additionally, indium tin oxide nanoparticles were added to increase the contact area between SnS2 and the electrode surface and thereby improve charge separation for photobioelectrocatalytic water oxidation. We tested the nanostructured anode electrodes under different applied potentials and irradiance intensities from a solar simulator to find the optimal photonic and faradaic efficiencies. Abstract : The catalytic system SnS2 ‐ThLc‐ITOnp is successfully combined with a fluorine‐doped tin oxide electrode to oxidize water under mild external applied potential conditions. (ThLc= Trametes hirsuta laccase; ITOno=ITO nanoparticles)